1983
DOI: 10.3109/00365598309179798
|View full text |Cite
|
Sign up to set email alerts
|

Xanthogranulomatous Pyelonephritis with Renocolic Fistula and Coexistent Contralateral Renal Carcinoma

Abstract: The presence of contralateral renal tumour in a case eventually found to have Xanthogranulomatous Pyelonephritis (XP) resulted in a wrong preoperative diagnosis of tumour with bowel fistula. The patient's prior history of bladder tumour and multiple renal cysts is also discussed, along with the retrospective finding of very minor changes in an early angiogram.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

1986
1986
1994
1994

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…Malek and Elder (1978) reported a patient with post-operative duodenocutaneous and colocutaneous fistulae. Tolia et al (1980) described a patient with XPN and persistent nephrocutaneous fistula and List et al (1983) reported a cast: of XPN with a renocolic fistula. Friedland et al (1983) described fistulae extending to other par1 s of the urinary tract, the gastrointestinal tract, the skin (even extending to unusual sites such as the buttock or axilla) and the lung.…”
Section: Discussionmentioning
confidence: 99%
“…Malek and Elder (1978) reported a patient with post-operative duodenocutaneous and colocutaneous fistulae. Tolia et al (1980) described a patient with XPN and persistent nephrocutaneous fistula and List et al (1983) reported a cast: of XPN with a renocolic fistula. Friedland et al (1983) described fistulae extending to other par1 s of the urinary tract, the gastrointestinal tract, the skin (even extending to unusual sites such as the buttock or axilla) and the lung.…”
Section: Discussionmentioning
confidence: 99%
“…Patients are typically in the fifth or sixth decade and the occurrence of pediatric cases, with peculiar aspects of the disease, is quite exceptional [29,38], Females are more frequently involved than males because of the higher incidence of urinary tract infections, and a 2:1 ratio has been reported [2], Renal cell carcinoma has occasionally been found to be associated with XGP [17,21,27].…”
Section: Discussionmentioning
confidence: 99%
“…Es zeigt sich ein Druck-und Klopfschmerz in der betroffenen Flanke bei oft palpablem Tumor. Langdauernde Krankheitsverläufe können in selteneren Fällen mit der Ausbildung von Fistelgängen (reno-kolisch, reno-kutan, uretero-kolisch) und Arthritiden einhergehen (6,12,22,24,32,33,40).…”
Section: Klinische Symptomatikunclassified